(untitled) (Research, Society and Development, 2022)
Objective: To report the experience of nursing students in an educational activity to promote health with patients in a psychiatric hospital based on Dorothea Orem’s theory. Methodology: Descriptive, qualitative, experience report type study, with the purpose of describing the health education activities, carried out by nursing students in December 2019. Results: The activity took place with the presentation of audiovisual content, built by the academics, which addressed the topic of personal hygiene. And to fix the debates, a playful strategy was developed with questions and answers. In this action, it was possible to apply the self-care promotion of Orem’s theory initially. Final considerations: This study presents an understanding of the relevance of educational actions in mental health since it is possible to observe in the practices immediate responses to the methodological strategies implemented for self-care. Activities of this nature reinforce care based on the role of clients as influencers of their well-being.